Multicultural ministry handbook : connecting creatively to a diverse world - Anderson, David A., 1966-; Cabellon, Margarita R. (Downers Grove, Ill. : IVP Books, 2010)
Drawing on the pioneering expertise of Bridgeway Community Church and BridgeLeader Network, the contributors present a holistic and multifaceted portrait of what a dynamic, grace-filled and diverse ministry can look like. --from publisher description.
The building blocks of a multicultural ministry / David A. Anderson -- Relational training for a multicultural church / Frank V. Eastham, Jr. -- Lessons learned by a White pastor in a multicultural church / Dave Michener -- Pastoral care and education / Dan Taylor -- Creative arts and multicultural ministry / Rich Becker -- Multicultural worship / Nikki Lerner -- Multicultural prayer ministry / K.C. Whang -- Multicultural children's ministry / Karen Eastham -- Multicultural student ministry / Jared Sorber -- Community outreach / Dave Michener -- Going further / Margarita R. Cabellon.
Includes bibliographical references.
Keywords: Church work with minorities -- United States; Race relations -- Religious aspects -- Christianity; Multiculturalism -- Religious aspects -- Christianity; Bridgeway Community Church (Columbia, Md.)